(untitled) (Global Journal of Medical Research, 2014)
Introduction-Depression has been increasingly diagnosed in the college age population with the American College Health Association reporting 16% of all college students having been diagnosed with depression.1 In another large survey of American college students, over half reported some depressive symptoms since entering college.2 Correspondingly, the percentage of all people treated with antidepressants grew over the past two decades. On college campuses in the United States, the numbers of prescriptions for antidepressants increased between the early 1990s and 2005, with estimates as high as 25-50% of the college students being seen in student health counseling centers being medicated with antidepressants.